2016
DOI: 10.3329/bjsir.v51i1.27064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of yield stability of maize inbred lines in multi-environment trials

Abstract: Stable performance of maize hybrids at a specific growing region is critical for obtaining high and stable yield. The objectives of this study were to assess grain yield stability of fourteen maize inbred lines from five different diverse regions of Bangladesh during 2010 -2011 growing season (rabi) using genotype main effect plus genotype by environment interaction (GGE) biplot and to identify maize inbred lines that have both high mean yield and stable yield performance across test environments of Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The AMMI result also showed that the first and second Interaction Principal Component Axis (IPCA1 and IPCA2) explained about 86.2% of the interaction sum squares, indicating that the first two IPCA are sufficient to explain GEI in grain yield of maize genotypes. This result is in harmony with some previous findings (Nzuve et al, 2013;Kumar and Singh, 2015;Kumar et al, 2014;Miah and Uddin, 2016); they indicated that AMMI with only two interaction principal component axes was the best predictive model. IPCA1 captures about 91.0% of the interaction sum of squares and the rest 9% were captured by IPCA2.…”
Section: Ammi Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…The AMMI result also showed that the first and second Interaction Principal Component Axis (IPCA1 and IPCA2) explained about 86.2% of the interaction sum squares, indicating that the first two IPCA are sufficient to explain GEI in grain yield of maize genotypes. This result is in harmony with some previous findings (Nzuve et al, 2013;Kumar and Singh, 2015;Kumar et al, 2014;Miah and Uddin, 2016); they indicated that AMMI with only two interaction principal component axes was the best predictive model. IPCA1 captures about 91.0% of the interaction sum of squares and the rest 9% were captured by IPCA2.…”
Section: Ammi Analysissupporting
confidence: 91%
“…The closer the genotypes to the center in AMMI2 biplot are assumed to be more stable than the genotypes far away from the center. AMMI model does not provide a quantitative stability measure and is indispensable to quantify and rank genotypes in terms of yield and stability; however, ASV quantifies and ranks genotypes (Kumar and Singh, 2015;Yong-Jian et al, 2010;Shiri, 2013;Sumathi and Govintharaj, 2017;Mortazavian et al, 2014;Miah and Uddin, 2016).…”
Section: Ammi-2 Relationships Among Genotypes and Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G × E interaction is recorded in the most significant trials and then modelled statistically and clarified. GEI modifies the hybrids' good seed performance in various environments so that choosing the correct genotype is very important [6]. In meta-environments, Modeling G × E interaction facilitates explaining the stability of breeding materials.…”
Section: Introductionmentioning
confidence: 99%
“…In most trails, the G × E interaction was witnessed and then modeled statistically and elucidated. Genotype × environment interaction adjusts the reasonable grain yield of genotypes in diverse environments and makes it hard to select the better ones [ 5 ]. Multilocation and multiyear trials can help identify superior and sustainable genotypes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%